2004
DOI: 10.1016/j.cub.2004.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Abl Kinases in T Cell Receptor Signaling

Abstract: We conclude that the Abl kinases have a role in the regulation of TCR-mediated signal transduction leading to IL-2 production and cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 37 publications
5
110
0
Order By: Relevance
“…The CrkL protein has been observed with a total of 28 PTMs identified in MS experiments (see www.phosphosite.org), however only phosphorylated tyrosine 207 (pTyr207) has been validated (using a range of methods including western blot, site-directed mutatgenesis and flow cytometry 30,[49][50][51][52][53][54] ). Tyrosine 207 phosphorylation has been shown to be the principle phosphorylation event related to BCR-ABL activity 30 .…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…The CrkL protein has been observed with a total of 28 PTMs identified in MS experiments (see www.phosphosite.org), however only phosphorylated tyrosine 207 (pTyr207) has been validated (using a range of methods including western blot, site-directed mutatgenesis and flow cytometry 30,[49][50][51][52][53][54] ). Tyrosine 207 phosphorylation has been shown to be the principle phosphorylation event related to BCR-ABL activity 30 .…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…38 A recent study has described the requirement of ABL kinases in TCR signal transduction. 11 Imatinib, by inactivating c-ABL, led to decreased phosphorylation of ZAP70 and LAT. This resulted in reduced activation of transcription factors, causing a decreased T-cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of ABL kinases in TCR signal transduction and T-cell viability is further confirmed by ABL-deficient mice, which show thymic and splenic atrophy and substantial T-and B-cell lymphopenia. 9,11 However, there are currently no indications that c-ABL may be regulated differently in naive and memory CTLs. In contrast, another study has reported that in memory CD8 ϩ T cells Lck expression is increased and associated with the CD8 coreceptor, whereas in naive CD8 ϩ T cells Lck is homogenously distributed in the cytoplasm and must first be recruited to the CD8 coreceptor upon TCR stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents cause growth arrest, apoptosis and decreased cell migration in EGFR-expressing basal keratinocytes through inhibition of the mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase (PI3K)-Akt and Janus kinase (JAK)-STAT (signal transducer and activator of transcription) pathways 98 . Finally, imatinib has significant but pleiotropic effects on the immune system, including inhibition of T-cell proliferation and activation [99][100][101][102][103] , impaired monocyte 104 and natural killer cell 105 function, and increased antigen presentation by dendritic cells 106 . The target or targets underlying these effects are unclear, but may include ABL1/2 and/or the T-cell-receptor-associated tyrosine kinases ZAP70 and SYK.…”
Section: Box 2 | Non-cardiac Toxicity With Tyrosine-kinase-targeting mentioning
confidence: 99%